Association of hemoglobin A1c variability and the incidence of heart failure with preserved ejection fraction in patients with type 2 diabetes mellitus and arterial hypertension - Gu, Jun; Fan, Yu-Qi; Zhang, Jun-Feng; Wang, Chang-Qian (Hellenic journal of cardiology, 2018)
This study aimed to investigate the association between variability in hemoglobin A1c (HbA1c) and left ventricular (LV) diastolic function and incidence of symptomatic heart failure with preserved ejection fraction (HFpEF) in patients with type 2 diabetes mellitus (T2DM) and arterial hypertension. A retrospective cohort study was conducted on eligible patients with T2DM and hypertension and without clinical signs or symptoms of heart failure in our hospital medical record database. Variability in HbA1c was measured by standard deviation (SD) and coefficient of variation (CV). Risk of new onset of symptomatic HFpEF was evaluated by multivariable cox regression analysis. A total of 201 subjects were categorized according to the median value of HbA1c variability indicators. Over a median follow-up of 7.3 years, the percentage of subjects who had new incidence of symptomatic HFpEF was higher in those with higher HbA1c-SD level (5/105 vs. 13/96, P=0.029) and higher HbA1c-CV level (5/101 vs. 13/100, P=0.046). Multivariable cox regression analysis also showed that higher HbA1c variability [HbA1c-SD (HR 1.754, 95% CI: 1.003-3.104, P=0.049) or HbA1c-CV (HR 1.604 95% CI: 1.064-2.419, P=0.024)] was associated with the presence of new-onset symptomatic HFpEF, independent of HbA1c-mean level, in T2DM and hypertensive patients. Moreover, lower HbA1c variability generated more prominent improvement in LV diastolic function (E/E′) during the follow-up. HbA1c variability may provide additional valuable information as a potential predictor of the progression of HFpEF in T2DM and hypertensive patients. [Display omitted]